UTILIZATION OF WORLDVIEW-3 SATELLITE IMAGES FOR 3-DIMENSIONAL (3D) MAPPING AS VISUALIZATION OF TOURISM AREA, KAYU ARO SUB-DISTRICT - Achmad Fahri; Dilla Angraina (Remote Sensing Technology Study Program, 2021)
One of the efforts to develop and improve the implementation of tourism is through the construction of objects and attractions, either in the form of working on existing tourist objects or creating new objects as tourist attractions. This study aims to map the Tourism Object Area of ​​Kayu Aro District for the tourism sector in the Kayu Aro District, Kerinci Regency, Jambi Province. The method used is descriptive with a quantitative approach. Quantitative research uses image data of description information about tourist objects found in the Tourism Object Area of ​​Kayu Aro District. The final result of this study is a 2-Dimensional Map and 3-Dimensional Visualization of the Tourism Object Area of ​​Kayu Aro District in the tourism sector, Kayu Aro District, Kerinci Regency, Jambi Province.